Table of Integration Model for Motor Vehicle Sharia Insurance - Rini Cahyandari; Asep Solih Awalluddin; Dara Selvi Mariani; Sukono Sukono; Puspa Liza Ghazali (Department of Mathematics, Faculty of Sciences and Technology, UIN Syarif Hidayatullah, 2020)
AbstractMotor vehicle insurance is one of the general insurance types that provide coverage for loss, damages, and disappearance of a motor vehicle due to risks experienced by the covered object. The product illustration of motor vehicle insurance is generally presented in a condensed form, containing few pages and limited information. Based on a product illustration of motor vehicle sharia insurance issued by PT. Asuransi Tri Pakarta (TRIPA) treated as a case study, an alternative version of product illustration in form of a table of integration model was designed to not only provided general information but also vehicle prices, values of premiums, tabarru, ujrah, investment, insurance costs, and surplus (if any). The partitions also performed on the additional protection offered by TRIPA so that the benefits that would be received by the insured would be greater. The generated table of integration model presents richer information regarding the insurance products, better scheme, and transparency in the management of total premiums.Keywords: general insurance; product illustration; management of total premiums; integration model; benefits. AbstrakAsuransi kendaraan bermotor merupakan salah satu jenis asuransi umum yang memberikan jaminan terhadap kerugian, kerusakan dan kehilangan kendaraan bermotor akibat terjadinya risiko yang menimpa obyek pertanggungan. Umumnya ilustrasi produk asuransi kendaraan bermotor disajikan dalam bentuk ringkasan yang beragam dalam beberapa halaman dan hanya menjelaskan informasi secara umum saja. Mengambil studi kasus berupa ilustrasi produk asuransi syariah kendaraan bermotor dari PT. Asuransi Tri Pakarta (TRIPA), dirancang bentuk alternatif penyajian berupa tabel model integrasi yang memberikan informasi tidak hanya harga kendaraan dan besaran premi, tetapi juga informasi tentang tabarru, ujrah, investasi, biaya asuransi, surplus (jika ada). Selanjutnya, dilakukan partisi terhadap perlindungan tambahan sehingga manfaat yang diperoleh tertanggung lebih luas. Melalui tabel model integrasi ini, informasi yang tertulis tentang produk asuransi lebih lengkap dan skema pengelolaan premi total asuransi syariah kendaraan bermotor juga lebih jelas.Kata Kunci: asuransi umum; ilustrasi produk; pengelolaan premi total; model integrase; manfaat.